Reevaluation of the contributions of reactive intermediates to the photochemical transformation of 17β-estradiol in sewage effluent - Lian, Lushi; Miao, Chenyong; Hao, Zhenyu; Liu, Qian; Liu, Yingjie; Song, Weihua; Yan, Shuwen (Water research (Oxford), 2021)
•The reaction rate constants of PPRIs with E2 were measured at various pH.•EfOM can act as a photosensitizer and an inhibitor in the phototransformation of E2.•Solar photodegradation can reduce the risk of endocrine disruption impacted by E2. Photodegradation of the natural steroid 17β-estradiol (E2), an endocrine-disrupting hormone that has been widely detected in aquatic environments, was investigated in wastewater effluents at various pH ranges under simulated solar irradiation. The rate of E2 degradation in the sewage effluents was stable at pH 6.0-7.0 but suddenly increased from pH 8.0-10.0. The second-order reaction rate constants of E2 with 3EfOM* and CO3•− were measured to increase 11.0-fold and 18.0-fold from pH 6.0 to 10.0, respectively. Two main reasons are proposed for this sharp increase. First, the change in the ionization state of E2 made it susceptible to oxidation by triplet-state effluent organic matter (3EfOM*) and carbonate radicals (CO3•−). Second, the steady-state concentration of CO3•− increased with increasing pH. Indirect photolysis was suggested to be the main degradation pathway in the sewage effluents, and 3EfOM* was proposed to play a major role at pH 8.0-9.0, while CO3•− played a significant role at pH 10.0. In this study, EfOM was shown for the first time to inhibit the oxidation of E2 initiated by 3EfOM* and CO3•−. Thus, we suggest that EfOM plays a dual role in the photodegradation of E2: EfOM can not only be activated as 3EfOM* to degrade E2 but also can inhibit the degradation of E2 by reducing the E2 oxidation intermediate back to E2. The estrogenic activity of the photodegradation products was also studied. The in vitro estrogenic activity of E2 solutions decreased approximately as fast as the E2 photodegradation occurred in the effluent water at various pH values, suggesting that solar photodegradation in sewage effluents reduces the risk of endocrine disruption in waters impacted by E2 and subject to continuing inputs. The results of this study are important for predicting the environmental fate of endocrine-disrupting chemicals and developing methods for their removal from aquatic environments. [Display omitted]